Are avoidance diets still warranted in children with atopic dermatitis?. Issue 1 (1st August 2019) - Eigenmann, Philippe A.; Beyer, Kirsten; Lack, Gideon; Muraro, Antonella; Ong, Peck Y.; Sicherer, Scott H.; Sampson, Hugh A.
Abstract: Nearly 40% of children with moderate‐to‐severe atopic dermatitis (AD) have IgE‐mediated food allergy (FA). This clinical observation has been extensively documented by experimental data linking skin inflammation in AD to FA, as well as by food challenges reproducing symptoms and avoidance diets improving AD. Although food avoidance may improve AD, avoidance diets do not cure AD, may even have detrimental effects such as progression to immediate‐type allergy including anaphylactic reactions, and may significantly reduce the quality of life of the patient and the family. AD care should focus upon optimal medical management, rather than dietary elimination. Food allergy testing is primarily indicated when immediate‐type allergic reactions are a concern. In recalcitrant AD, if food is being considered a possible chronic trigger, a limited panel of foods may be tested. An avoidance diet is only indicated in patients clearly identified as food allergic by an appropriate diagnostic food challenge, and after adequately informing the family of the limited benefits, and possible harms of an elimination diet.